2019
DOI: 10.3390/molecules24061076
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones

Abstract: Phytoestrogens are naturally occurring nonsteroidal phenolic plant compounds that, due to their molecular structure and size, resemble vertebrate steroids estrogens. This review is focused on plant flavonoids isoflavones, which are ranked among the most estrogenic compounds. The main dietary sources of isoflavones for humans are soybean and soybean products, which contain mainly daidzein and genistein. When they are consumed, they exert estrogenic and/or antiestrogenic effects. Isoflavones are considered chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
422
0
30

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(453 citation statements)
references
References 243 publications
(357 reference statements)
1
422
0
30
Order By: Relevance
“…To the fact that identification of all aspects of molecular mechanisms of isoflavones present in legumes influence on mineralization is quite complicated, for the beginning we chose isoflavones interactions with RANKL and their possible influence on functional mineralization process in Saos-2 cells. The mechanism of isoflavones effect on osteoclasts probably does not depend on estrogen mechanisms, as there are no ERs in the osteoclast nuclei [25]. Presented results are necessary and basal for our further studies and they do not exclude involvement of different types of signaling transduction pathways.…”
Section: Effect Of Isoflavones On Saos-2 Viability and Mineralizationmentioning
confidence: 81%
See 1 more Smart Citation
“…To the fact that identification of all aspects of molecular mechanisms of isoflavones present in legumes influence on mineralization is quite complicated, for the beginning we chose isoflavones interactions with RANKL and their possible influence on functional mineralization process in Saos-2 cells. The mechanism of isoflavones effect on osteoclasts probably does not depend on estrogen mechanisms, as there are no ERs in the osteoclast nuclei [25]. Presented results are necessary and basal for our further studies and they do not exclude involvement of different types of signaling transduction pathways.…”
Section: Effect Of Isoflavones On Saos-2 Viability and Mineralizationmentioning
confidence: 81%
“…Intake of biochanin A in foods is additionally supported by the fact that biochanin A blood level has been shown to be higher when consumed in the presence of other isoflavones [24]. Intake of isoflavones may be particularly beneficial in preventing osteoporosis when they are additionally accompanied by proteins of both plant and animal origin [25]. Numerous previous studies have indicated that soybean, the most commonly consumed legume rich in phytoestrogens such as genistein and daidzein glycosides, has osteogenic activity.…”
Section: Energetic Effects Of Rankl-isoflavones Interactionsmentioning
confidence: 99%
“…Daidzein, a natural compound easily found in soybeans and a number of plants, has been reported for its pharmacological activity in the prevention and therapy of cardiovascular disease, several types of cancer, osteoporosis and menopausal symptoms [88]. Due to its low water solubility and first-pass metabolism, daidzein shows poor oral BA [89].…”
Section: Daidzeinmentioning
confidence: 99%
“…From a molecular standpoint, genistein seems to exert pleiotropic effects, being able to activate various DNA damage checkpoints, promoting cell cycle arrest, mitotic catastrophe and cell death (depleting G1 population of cells, leading to an accumulation at G2/M and activating the apoptotic cascades, up-regulating caspase-3 and caspase-7 as well as p38/MAPK and ATM/Chk2/Cdc25C/Cdc2, and down-regulating the Bcl-2-Bax and NF-κB/p65 complexes) [53][54][55]. Furthermore, genistein finely tunes different angiogenetic cascades [56,57].…”
Section: Brca1 Diet and Breast Cancermentioning
confidence: 99%